California State University Channel Islands Revised Brand Foundation - ADV Market Research and Consulting:::::: (2023)
CSUCI is an inspiring, supportive, opportunity-rich Central Coast university committed to life-changing, applicable education that engages students in a community that is both challenging and comfortable.